Inovasi Pembuatan Kertas Dari Daun Jati Sebagai Solusi Ramah Lingkungan Dalam Industri Kertas - Roudlotul Jannah; Nur Sa’adatut Daraini; Onggo Dwi Pracoyo; Abd. Raid Sopalatu; Maulana Ahmad Ramdhani; Sustian Alfina; Rizki Ananda Agust Lailita; Jahroni Jahroni; Laila Badriyah (FKIP, Universitas Palangka Raya, 2025)
Krian Regency is famous for its forest products, especially teak trees, whose valuable wood is often used to make furniture. This research aims to develop a process for making environmentally friendly paper from dried teak leaves using the Participatory Action Research (PAR) method. The PAR approach was chosen so that the local community could be actively involved in every stage of the research, from collecting materials, processing teak leaves, to the paper making process. This method is implemented through several stages, namely problem identification, action planning, implementation, observation and evaluation. Other parts of teak trees, such as leaves, have not been fully utilized. Young teak leaves are widely used as food wrappers and to make natural dyes. Teak leaves are abundant in the dry season but are not widely used. Dried teak leaves are a source of natural fiber that is cheap and easy to obtain. This investigation will process dried teak leaf waste into processing paper. This activity uses the PAR method. Teak leaves are processed into pulp using NaOH and soda process. Art paper is made from paper pulp. Researchers must conduct more research to find out that teak leaves as a natural resource can increase value and sustainability. Products made from teak leaves can not only increase the income of people in the area, but can also be used to improve environmental sustainability. The community can help reduce excessive tree felling and maintain environmental balance by utilizing natural waste.